(untitled) (Rabi Sangyan, 2024)
This study investigates the influence of behaviour on job stress among employees in commercial banks in Eastern Nepal, focusing on the dimensions of role clarity, communication, delegation, motivation, and social support. A survey-based approach was employed, collecting data from 210 respondents in Eastern Nepal’s banking sector. Descriptive statistics, correlation, and regression analysis were conducted using SPSS to assess the relationship between supervisory behavior and job stress. The results indicate significant relationships between all dimensions of supervisory behavior and job stress, with role clarity and communication emerging as the most influential factors. Five hypotheses were tested, confirming that higher levels of the clarity and communication associated with reduced job stress, while social support, delegation, and motivation also play a positive but lesser role. Effective supervisory practices, particularly in role clarity and communication, are crucial for instigating job stress among employees in Eastern Nepal’s commercial banks. Enhancing these supervisory behaviors can foster a healthier work environment and improve employee well-being.